Higher Serum Levels of Interleukin 10 Occur at Onset of Acute Otitis Media Caused by Streptococcus Pneumoniae Compared to Haemophilus Influenzae and Moraxella Catarrhalis. (12th February 2013) - Liu, Keyi; Kaur, Ravinder; Almudevar, Anthony; Pichichero, Michael E.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis Acute otitis media (AOM) involves an inflammatory response to microbes in the middle ear that facilitates clearance of otopathogens. Clinically, Streptococcus pneumoniae (Spn) infections of the respiratory tract are characterized by greater inflammatory responses than nontypeable Haemophilus influenzae (NTHi) and Moraxella catarrhalis (Mcat). Interleukin 10 (IL‐10) plays an important role in down‐regulating the inflammatory response. We compared serum IL‐10 levels in children before onset, at onset, and after recovery from AOM caused by Spn, NTHi, and Mcat. We sought to determine if IL‐10 could serve as a biomarker to distinguish AOM caused by Spn versus NTHi and Mcat. Study Design Prospective, longitudinal study in a primary care pediatric practice in Rochester, NY. Methods Participants were 54 children, 6 to 30 months of age. Outcomes measured were serum IL‐10 levels when healthy, at onset of AOM, and after recovery from AOM. Results Serum IL‐10 was elevated when children developed AOM (P=0.013) due to infections caused by Spn (P=0.011) but not AOM caused by NTHi or Mcat. Middle ear fluid levels of IL‐10 mirrored those seen in serum but were 10‐fold higher (P=0.02). Other effector cytokines in serum: IL‐4, IFN‐γ, and TNF‐alpha, did not show the same increases as IL‐10 at onset of AOM. Conclusion Our study indicates that AOM caused by Spn elicits a significantly higher IL‐10 response compared to NTHi and Mcat and may prove to be a biomarker of AOM infections by Spn. Level of Evidence 4.